Public and Media Spheres in Communication and Health - Petracci, Mónica (2015)
Health Communication is a field of knowledge, which is in a growing and strengthening process at present. The aim of this article is to analyze three qualitative studies about communication and health articulations conducted in Buenos Aires, Argentina: to communicate a message of health promotion in a public hospital; to communicate public policies in the Ministry of Health, Argentina; and, finally, to communicate health news on the press. Semi-structured interviews were conducted with health care providers, decision makers and journalists, respectively. Findings show how Health Communication contributes to building citizenship and social participation.